Abnormal shifts in Raman spectra of deuterated cytidine and 6-azacytidine. Issue 3 (2010) - Garasevych, S.; Iakhnenko, M.; Slobodyanyuk, O.; Vaskivskyi, I.
Abstract : It was revealed that some peaks in Raman spectra of cytidine, 6-azacytidine (6-azaC), and cytosine dissolved in D2 O are shifted to high frequencies in respect to their positions in spectra of H2 O solution. Such "blue shifts" occur due to deuteration of the nucleoside molecule itself but not due to effect of deuterated solvent. This conclusion is deduced from observation of blue (abnormal) shift in Raman spectra of cytidine and 6-azaC microcrystals recrystallized from D2 O solution. Both normal and abnormal shifts close to the experimentally observed were obtained in the calculated spectra of 6-azaC and cytidine. We assume that abnormal shifts may be caused by substitution of intramolecular H-bonds with D-bonds.